Legal Protection for Domestic Workers: The Experience of Indonesia - Sakka Pati (Hasanuddin Law Review, 2019)
Given its social and economic invisibility and the accompanying low social status, domestic work is often exploitative. This research was aimed to find out and formulate the substance of legal protection for domestic workers in legislation in the field of labor in terms of the perspective of justice. It uses a statute, case, and socio-legal approaches. It was conducted in 3 (three) major cities, namely Jakarta, Yogyakarta and Makassar. The results of research showed that the substance of legal provisions in general for the protection of domestic workers, especially in labor legislation basically has not been able to guarantee justice and legal certainty because the responsibility of State has not been implemented in the existing legal substance. The paradigm of harmonization and the principles of legal agreements in the field of labor have not guaranteed justice and legal certainty for domestic workers. It is evidenced by the view of the profession of domestic workers who are positioned as informal workers, in addition they are not being accommodated as an element protected by law, it is also related to the protection of basic rights and labor social security does not cover the existence of domestic workers.